Go Delivery in Producing Online-Based Police Records (SKCK) to Achieve South Sumatra Polda Service Performance - Luthfi, Ahmad; Sobri, Kgs M.; Lionardo , Andries; Putra, Raniasa (Universitas Medan Area, 2024)
This study aims to examine and deploy an online document delivery service, named